Shapley's value for fuzzy games - Alvarado Sibaja, Raúl (1998)
This is the continuation of a previous article titled “Fuzzy Games”, where I defined a new type of games based on the Multilinear extensions f, of characteristic functions v for  cooperative  games.   We  showed  that f fulfills  the  definition  of  characteristic functions and most of standard theorems for cooperative games also hold for this new type of games: The fuzzy games. Now we give some other properties and the extension of the definition of Shapley’s Value for Fuzzy Games